ANALISIS PENGELOLAAN DANA DESA(Studi Kasus di Desa Singopuran Kecamatan KartasuraKabupaten Sukoharjo Tahun 2016) - RIYANI, NUNUK, Dr. Bambang Sumardjoko, M.Pd (2016)
This research aimed to describe The Allocation of Management Village Fund located in Singopuran Village, KartasuraSub-Distric, Sukoharjo Regency which covered the management, usage, and the Evaluation of Village Fund. This research is qualitative research by using case study strategy. The technique of collecting data is conducted by using several techniques such as interview, observation, and documentation. The researcher used data triangulation and technique of collecting data to verify the validity of the data. The researcher used interactive analysis by means of collecting, reducing, presenting the data, and making conclusion. The result of this research shows that The Allocation of Management Village Fund located in Singopuran Village, Kartasura Sub-Distric, Sukoharjo Regencyhas been used wisely as planned for the development of the village but still needs an evaluation to be fix. Meetings conducted to formulate the development and resurfacing which should be built.